Strategic Controls and Learning Orientation: A Formula for Innovation and Success in Indonesia’s Creative Economy - Arfah Piliang; Rahma Yulita; Masril Masril (Poltanesa, 2026)
This quantitative research evaluates how learning orientation, diagnostic control systems, and interactive control systems impact product innovation and company performance within the creative economy context in Indonesia. The rapid growth of Indonesia’s creative industry faces ongoing challenges regarding product innovation development, and corporate performance enhancement. To investigate these dynamics, data were gathered both in person and online from three hundred and thirty-two owners and managers of the traditional Songket weaving industry across Riau, South Sumatra, and West Sumatra. Structural Equation Modeling Partial Least Squares was utilized as the primary analytical instrument to measure the relationships between the variables. The findings demonstrate that learning orientation significantly and positively affects both product innovation and company performance. Additionally, interactive control systems positively influence product innovation, while diagnostic control systems focus more on operational efficiency and goal achievement. Product innovation is also proven to directly enhance company performance and substantially mediate the relationships between both control systems and firm performance. Practitioners should cultivate an organizational learning culture and implement flexible management control systems, while future researchers should consider external factors such as market dynamics and government policies